2017
DOI: 10.1002/slct.201701122
|View full text |Cite
|
Sign up to set email alerts
|

Substituent‐Controlled Selective and Sensitive Potential Optical Fluoride Sensors Based on Salicylidene Schiff Base Derivatives

Abstract: A series of colorimetric chemosensors 2‐((anthracen‐9‐ylmethylene)hydrazonomethyl)phenol (1) and its derivatives with electron donating (–tBu, 2) and withdrawing groups (–Cl, 3) have been synthesized for selective colorimetric ion sensing. Receptor 1 exhibits ability to colorimetric recognition of F− ions in aqueous environment without any interference of other anions revealed in UV‐vis study. Remarkable substituents effect has been observed in selective sensing as receptors 1 and 2 are exclusive colorimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In the rst step, the salicylidene -OH group which is involved in intramolecular hydrogen bonding with imine nitrogen (A in Scheme 2), forms an O-H/A À hydrogen bonded complex (B in Scheme 2). 16 The fact that the peak position of the salicylidene -OH proton in SL did not shi upon addition of halides (Cl À and Br À ) suggest that the intramolecular O-H/N hydrogen bond persists in the presence of these anions. However, broadening or disappearance of the salicylidene -OH peak in the presence of anions can be attributed to protonexchange processes in the solution-state.…”
Section: Resultsmentioning
confidence: 99%
“…In the rst step, the salicylidene -OH group which is involved in intramolecular hydrogen bonding with imine nitrogen (A in Scheme 2), forms an O-H/A À hydrogen bonded complex (B in Scheme 2). 16 The fact that the peak position of the salicylidene -OH proton in SL did not shi upon addition of halides (Cl À and Br À ) suggest that the intramolecular O-H/N hydrogen bond persists in the presence of these anions. However, broadening or disappearance of the salicylidene -OH peak in the presence of anions can be attributed to protonexchange processes in the solution-state.…”
Section: Resultsmentioning
confidence: 99%
“…[60][61][62] The molecular switching properties of Schiff base sensors have been applied in the construction of molecular keypads and logic gates. 63,64 In the past, significant research work has been done in developing fluorescent Schiff base sensors for metal ion detection. 63,[65][66][67][68][69][70][71] However, to the best of our knowledge, no review has been reported on metal ion detection using fluorescent Schiff base sensors.…”
Section: Introductionmentioning
confidence: 99%
“… 29–41 The chemosensors based on a hydrogen-bond strategy are usually disturbed by other basic anions such as H 2 PO 4 − and AcO − because they have similar surface charge density and basicity to F − . 42 In addition, the increase of the ionic strength and hydration enthalpy of F − in water often makes the hydrogen bond ineffective in aqueous medium. 43 The chemosensors based on B–F complexation can detect F − in drinking water and fluorine-containing chemical agents, but their cytotoxicity limits their biological applications.…”
Section: Introductionmentioning
confidence: 99%